Multidisciplinary Nursing, Pharmacological, and Radiologic Perspectives in the Assessment and Management of Arachnoid Cysts - Almutairi, Fatimah Mutairan; Asrar Mohammed Faqih; Badryah Ghabran Ahmed Ghazwani; Hanan Abdu Yahy Matari; Marzuq Quedan Aleutaybi; Faisal Mohammed Saifi Aljabri; Dhoha Mohammed Daba; Esaam Mohammed Abdullah Shaker; Haya Tulihan Alenezi; Anoud Owead Alanzi; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Arachnoid cysts are benign, cerebrospinal fluid (CSF)-filled sacs that develop within the arachnoid membrane, representing one of the most common intracranial cystic lesions. They are predominantly congenital, arising from abnormal embryological development, and are most frequently located in the middle cranial fossa. While often discovered incidentally, a subset can become symptomatic due to mass effect or CSF flow obstruction. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This article provides a comprehensive, multidisciplinary overview of arachnoid cysts, focusing on their etiology, clinical presentation, diagnostic evaluation, and management principles to guide healthcare professionals in distinguishing incidental findings from clinically significant cases requiring intervention. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Diagnosis relies primarily on neuroimaging. Computed Tomography (CT) and Magnetic Resonance Imaging (MRI) are the mainstays, with cysts appearing as well-circumscribed, non-enhancing lesions that match CSF density/signal on all sequences. Advanced MRI techniques, such as cisternography and high-resolution T2-weighted imaging, are used to assess cyst communication with CSF spaces and for surgical planning. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The vast majority of arachnoid cysts are asymptomatic and stable, requiring only conservative monitoring with periodic clinical and radiologic follow-up. For the minority that cause symptoms like headaches, seizures, focal neurological deficits, or hydrocephalus, surgical intervention is indicated. Treatment options include endoscopic or microsurgical fenestration to create communication with CSF pathways or, less commonly, cystoperitoneal shunting. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A patient-centered, multidisciplinary approach is essential for optimal management. Most cysts are benign and require no treatment, but accurate diagnosis and timely surgical referral for symptomatic cases lead to excellent outcomes. Effective interprofessional collaboration among radiologists, neurologists, neurosurgeons, and nurses ensures appropriate patient education, surveillance, and intervention.